The effect of e-service quality on customer satisfaction and customer loyalty: A study on mobile banking application in Indonesia - Beanning, Lindsay; Zulkarnain (Communications in Humanities and Social Sciences, 2024)
In the current globalization, technology and information are one of the most rapidly developing aspects of world life. Technological advances facilitate customers and companies in many fields, one of which is in banking sector. Some banking transactions that can be done via the internet or online include fund transfers, payment of electricity/water bills and e-commerce, investment and top-up of credit/data packages.  In the last 5 years from January 2018 to April 2023, digital banking transactions in Indonesia grew by 158% as, for instance, seen in the growth of BNI Mobile Banking users in February 2023 reaching 14.03 million users. This number jumped 25% (YoY) when compared to the same period of the previous year by 11.22 million users. The effectiveness and efficiency of e-service quality in facilitating online shopping, buying, and delivery processes define its interaction with services. This concept encompasses two main dimensions: utilitarian and hedonistic. The utilitarian aspect focuses on practical elements such as security, privacy, and user-friendliness, while the hedonistic dimension is more subjective and individualized, emphasizing the enjoyment and emotional satisfaction derived from the shopping experience, rather than merely accomplishing a task. This aspect highlights the potential for pleasure and emotional value in both the process of shopping and the use of purchased items. This research used the PLS-SEM approach. The results of the analysis in this study revealed a number of variables that can optimally improve e-service quality and customer loyalty for BNI mobile banking in Indonesia.